1T MoS2 nanosheets with extraordinary sodium storage properties via thermal-driven ion intercalation assisted exfoliation of bulky MoS2. (July 2019) - Sun, Dan; Huang, Dan; Wang, Haiyan; Xu, Gui-Liang; Zhang, Xiaoyi; Zhang, Rui; Tang, Yougen; Abd EI-Hady, Deia; Alshitari, Wael; Saad AL-Bogami, Abdullah; Amine, Khalil; Shao, Minhua
Abstract: Metallic phase (1T) MoS2 has attracted enormous attention as an appealing energy storage material for batteries, supercapacitors, and catalysts. However, a facile fabrication method is lacking and the intensive understanding of its sodium storage mechanism is absent. Herein, ultrathin 1T MoS2 nanosheets (1–2 layers) are directly fabricated via and are investigated as an anode material for sodium-ion batteries. Interestingly, the as-prepared 1T MoS2 nanosheets demonstrate a high reversible capacity of 450 mAh g −1 at 50 mA g −1 and outstanding cycling stability with a high capacity retention ratio of 94% after 200 cycles at 1 A g −1, which is far superior to that of the 2H phase counterpart. Density function theory (DFT) calculations show that, in addition to significantly enhanced electronic conductivity, 1T MoS2 also possesses much more sodium philicity and faster Na atom mobility in comparison with the 2H phase. More importantly, as revealed by ex-situ Raman, in-situ X-ray diffraction, and DFT calculations, the 1T MoS2 is more capable of suppressing the dissolution of S species from the material structure compared with the 2H phase, leading to excellent cycling stability. The facile and easily scalable method as well as the deep mechanism analysis will provide a very important reference for the development of high-performance MoS2 anodes and other SIB electrode materials. Graphical abstract: Image 1 Highlights: Ultrathin 1T MoS2 nanosheets are directly fabricated from commercial bulky 2H MoS2 . The as-prepared 1T MoS2 demonstrates superior Na + storage properties. 1T MoS2 possesses higher Na philicity and faster Na atom mobility than the 2H phase. 1T MoS2 is more capable of suppressing the dissolution of S species.